(untitled) (Nigerian Journal of Physiological Sciences, 2025)
Dexamethasone (Dex) is a potent synthetic glucocorticoid with broad clinical applications, but systemic administration often leads to metabolic disturbances and cognitive side effects. Intranasal Dex has potential to deliver glucocorticoids directly to the brain, minimizing systemic side effects associated with traditional administration. However, its comprehensive effects on metabolic, behavioural, and neurochemical endpoints after repeated dosing remain unclear. Adult male mice were randomly assigned to four groups: control (saline) and dexamethasone (Dex) doses of 5, 15, or 50 μg/kg administered intranasally once daily for seven days. Peripheral measures included body weight, fasting blood glucose, glucose tolerance test (GTT), fasting serum and brain insulin levels, HOMA‑IR, and serum corticosterone via ELISA. Behavioural assays comprised the Morris Water Maze, Elevated Plus Maze, Open Field Test, and Novel Object Recognition Test. Brain homogenates were analysed for oxidative stress markers (superoxide dismutase, glutathione), cholinergic activity (acetylcholinesterase), and trace minerals (Zn, Fe, Ca). Intranasal Dex did not affect body weight, glycaemic control, insulin sensitivity, or corticosterone levels. Dose‑dependent declines in locomotor exploration and spontaneous alternation were observed, alongside increased escape latencies during spatial learning without altering memory retention or novel object recognition. Oxidative stress markers and global Zn, Fe, and Ca remained stable; however, acetylcholinesterase activity trended downward and variability in Fe and Ca emerged at higher doses. Seven-day intranasal Dex selectively impairs exploratory behaviour and learning acquisition through central glucocorticoid receptor–mediated synaptic and cholinergic modulation, while preserving peripheral metabolic and oxidative balance.